ANALISIS DAMPAK BELANJA DAERAH TERHADAP KUALITAS SUMBER DAYA MANUSIA - Alfi Nurintasya; Dwi Budi Santoso (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study is motivated by the state of human resources in Papua Province, as evidenced by the health and education indexes, which continue to lag behind the national average. Even in terms of health and education, the Province of Papua falls short of the Province of East Nusa Tenggara, which did not even receive special autonomy funds. The purpose of this study is to examine the impact of regional health and education spending on health and education quality in 29 districts/cities in Papua Province from 2011 to 2019. The 3SLS simultaneous equation model with panel data is used in the research analysis technique. According to the findings of this study, health spending has failed to improve health quality in Papua Province due to the high cost of access caused by uneven development of health facilities. Meanwhile, education spending has had a significant impact on improving education quality in Papua Province because educational facilities are more accessible to the general public, resulting in lower access costs. The research findings are expected to be useful in developing strategies to accelerate the development of qualified human resources in the Papua Province.